2015
DOI: 10.1080/09500693.2015.1085133
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Diverse Undergraduate Researchers’ Academic Outcomes and Perceptions of Their Research Mentoring Relationships

Abstract: Few studies have empirically investigated the specific factors in mentoring relationships between undergraduate researchers (mentees) and their mentors in the biological and life sciences that account for mentees’ positive academic and career outcomes. Using archival evaluation data from more than 400 mentees gathered over a multi-year period (2005–11) from several undergraduate biology research programs at a large, Midwestern research university, we validated existing evaluation measures of the mentored resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 47 publications
4
126
1
Order By: Relevance
“…Both virtual and face-to-face mentoring have been shown to increase exposure and retention [25]. At the faculty level, having (or having had) a formally designated mentor was identified as a significant predictor of high research productivity, second only to the faculty member being “internally driven to conduct research” [26].…”
Section: Mentorship Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…Both virtual and face-to-face mentoring have been shown to increase exposure and retention [25]. At the faculty level, having (or having had) a formally designated mentor was identified as a significant predictor of high research productivity, second only to the faculty member being “internally driven to conduct research” [26].…”
Section: Mentorship Mattersmentioning
confidence: 99%
“…For instance, some research has found that URM women in science and engineering were significantly more interested than their White counterparts in having discussions with their mentor about issues of race/ethnicity [39]. Byars-Winston et al [25] found that URM students were more likely than their predominantly White mentors to endorse that cultural diversity matters should be addressed in the research mentoring relationship [37]. Prunuske et al [40] found that mentors of URM mentees tended to espouse colorblind attitudes and the notion that cultural diversity is irrelevant to the research mentoring relationship [40].…”
Section: The Need To Study Mentoring Relationshipsmentioning
confidence: 99%
“…() utilizing a longitudinal quasi‐experimental design, provide evidence that quality mentorship (not ethnic similarity of mentor to protégé) contributed to retention and persistence of African American students drawn from 50 different institutions. Further, work by Byars‐Winston, Branchaw, Pfund, Leverett, and Newton, , which analyzed archival data from over 400 protégés collected from 2005 to 2011 from several undergraduate biology research programs, found that perceived mentor effectiveness indirectly predicted enrollment in science‐related doctoral or medical degree programs through research self‐efficacy. Mentor social support, a likely cue of kindness and belonging, may be particularly key for HU STEM students, which can impact student persistence through strengthening science identity (Hernandez et al., under review; Estrada, Zhi, & Gershon, in preparation).…”
Section: Current Research On Successful Approaches To Creating Socialmentioning
confidence: 99%
“…Ugrin and colleagues () found that among graduate students and their dissertation chairs, mixed gender dyads actually reported more publications than same‐gender dyads. However, a number of studies have found gender concordance to be relatively unimportant to mentee's performance or outcomes (Byars‐Winston et al., ; Campbell & Campbell, ; Carrington & Saggers, ; Kirchmeyer, ; Tenenbaum, Crosby, & Gliner, ). Finally, when studying gender matching in mentoring relationships, researchers have tended to focus on women mentees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although mentoring is one of the central elements of SUREs, positive consequences of mentoring are not universal (Schwartz, ). A number of scholars have studied mentoring relationships quantitatively to understand the conditions under which mentoring is most effective and to identify factors influencing the mentoring relationship (e.g., Aikens et al., ; Byars‐Winston, Branchaw, Pfund, Leverett, & Newton, ; Daniels et al., 2016; Eby, Lockwood, & Butts, ; Noe, ). Some have found that the frequency and quality of mentee‐mentor interactions are important (Daniels et al., 2016).…”
Section: Introductionmentioning
confidence: 99%